2021
DOI: 10.1108/cw-09-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

A new hyperchaotic system from T chaotic system: dynamical analysis, circuit implementation, control and synchronization

Abstract: Purpose The purpose of this paper is to develop new four-dimensional (4D) hyperchaotic system by adding another state variable and linear controller to three-dimensional T chaotic dynamical systems. Its dynamical analyses, circuit experiment, control and synchronization applications are presented. Design/methodology/approach A new 4D hyperchaotic attractor is achieved through a simulation, circuit experiment and mathematical analysis by obtaining the Lyapunov exponent spectrum, equilibrium, bifurcation, Poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This is a different approach that uses the fractional Lorenz equation set. Lately, there are popular studies on chaotic secure communication systems implemented by electronic components using active elements as op-amps [29], [30], current conveyor (CCII+) [31], [32], DVCCs [33] [34]. In May 1947, RAND corporation started creating random numbers by using an electronic simulation of a roulette wheel, and this study was published in 1955 as a random number book named A Million Random Digits with 100,000 Normal Deviates [35].…”
Section: Analysis and Applications Of A Hyperchaotic Systemmentioning
confidence: 99%
“…This is a different approach that uses the fractional Lorenz equation set. Lately, there are popular studies on chaotic secure communication systems implemented by electronic components using active elements as op-amps [29], [30], current conveyor (CCII+) [31], [32], DVCCs [33] [34]. In May 1947, RAND corporation started creating random numbers by using an electronic simulation of a roulette wheel, and this study was published in 1955 as a random number book named A Million Random Digits with 100,000 Normal Deviates [35].…”
Section: Analysis and Applications Of A Hyperchaotic Systemmentioning
confidence: 99%
“…Emiroglu et al [28] studied the problem of control of chaos in a ferroresonant circuit using backstepping nonlinear control to become stable in the equilibrium point and converge to the desired trajectory or point and demonstrated the effectiveness of designed control inputs for chaos control in ferroresonant phenomena. Then, Emiroglu et al [29] proposed a passive synchronization control method based on the new four-dimensional chaotic system to achieve the synchronization of the new four-dimensional chaotic system hyperchaotic system with different initial conditions. Alexander et al [30] designed a controller based on linear quadratic regulatory control and applied it to nonautonomous systems with infinite coexisting attractors, and the effectiveness of the controller was demonstrated through error.…”
Section: Introductionmentioning
confidence: 99%
“…The study of hyperchaotic systems was further developed in 1979 when Rössler discovered a four-dimensional hyperchaotic system [3]. Multidimensional chaotic and hyperchaotic systems became more well-known in the following years, providing useful applications in science and engineering [4]. Recently, there are many studies to be found in the literature on the dynamic analysis of chaotic systems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%